1992
DOI: 10.1182/blood.v80.9.2237.2237
|View full text |Cite
|
Sign up to set email alerts
|

Induction of differentiation of human mast cells from bone marrow and peripheral blood mononuclear cells by recombinant human stem cell factor/kit-ligand in long-term culture

Abstract: In the murine system, a number of cytokines (including interleukin-3 [IL-3], IL-4, and stem cell factor [SCF]) promote the growth of mast cells (MCs). However, so far little is known about factors controlling differentiation of human MCs. Recent data suggest that human MCs express receptors (R) for SCF. The aim of the present study was to investigate whether recombinant human (rh) SCF induces differentiation of human MCs from their precursor cells. For this purpose, bone marrow (BM; normal donors, n = 6) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(146 citation statements)
references
References 57 publications
6
137
0
1
Order By: Relevance
“…HS instead of FCS, 61 may be a possible explanation for our current ®ndings. Since both murine and human NGF have been shown to be biologically active in basophils 62 and since interspecies DNA sequences are highly homologous, 1 the use of murine NGF in the studies of Valent et al 61 are on the other hand unlikely to account for the negative ®ndings of these authors.…”
Section: Discussionmentioning
confidence: 99%
“…HS instead of FCS, 61 may be a possible explanation for our current ®ndings. Since both murine and human NGF have been shown to be biologically active in basophils 62 and since interspecies DNA sequences are highly homologous, 1 the use of murine NGF in the studies of Valent et al 61 are on the other hand unlikely to account for the negative ®ndings of these authors.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 On the other hand, SCF enhances histamine release from human mast cells after a brief incubation. [28][29][30] Probably, the mechanisms of the IFN-g-and SCF-induced enhancement of histamine release differ.…”
Section: Discussionmentioning
confidence: 99%
“…Nocka et al isolated a growth factor from conditioned medium of Balb/3T3 fibroblasts which had the biological properties expected of SCF [19]. It was shown that long-term incubation with SCF led to differentiation of human and murine MC from their precursor cells in the absence of fibroblasts [20,21]. In vivo, local administration of SCF promotes CTMC development in mouse skin, while its systemic administration in rats induces both CTMC and MMC development [22].…”
Section: Normal Fibroblast Microenvironmentmentioning
confidence: 99%